THE ROLE OF CUSTOMER SATISFACTION IN MEDIATING THE INFLUENCE OF E-SERVICE QUALITY ON CUSTOMER LOYALTY (Study of Maxim Service Users in Denpasar City) - Ni Made Prapti Astiti; Tjokorda Gde Raka Sukawati (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2024)
Customer loyaltyis the tendency of customers to repurchase products or services. Several factors that can grow customer loyalty are customer satisfaction and e-service quality. The aim of this research is to explain the role of customer satisfaction in mediating the influence of e-service quality on customer loyalty among Maxim service users. This research was conducted in Denpasar City, the number of samples in this study was 110 respondents using the purposive sampling method. Data collection was carried out by distributing questionnaires via Google Form. The data analysis techniques used are path analysis, Sobel test and VAF test. Based on the results of this research analysis, it shows that e-service quality has a positive and significant effect on customer loyalty, e-service quality has a positive and significant effect on customer satisfaction, customer satisfaction has a positive and significant effect on customer loyalty, customer satisfaction positively and significantly mediates the effect of e -service quality towards customer loyalty. Based on these results, the management of Denpasar City online transportation services is expected to pay attention to customer loyalty by considering e-service quality and customer satisfaction.